Nutritional status and the use of protease inhibitors among HIV-infected children in Klang Valley, Malaysia - Mohd Taib, Mohd Nasir; Yeo, J.; Lee, Mary Huang Soo; Koh, M. T.; Mohd Razali, Kamarul Azhar; Khor, Geok Lin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
This study determined the association between nutritional status and the use of protease inhibitors (PI) containing regimen among HIV-infected children receiving treatment at the referral centres in Klang Valley. A total of 95 children currently on antiretroviral (ARV) therapy, aged one to eighteen years, were recruited using purposive sampling. Demographic data, anthropometric measurements, medical history, were collected using a structured questionnaire. Serum micronutrients levels and lipid profile were also examined using blood samples. Mean age was 8.8 3.9 years and 44.2% were on PI. Age (2=10.351, p = .006), weight-for-age ( 2 = 6.567, p = .010), serum selenium ( 2 = 4.225, p = .040) and HDL-C (2=7.539, p=.006) were significantly associated with the use of PI. Fewer children on PI were deficient in selenium as compared to those not on PI. On the contrary, more children on PI were underweight and had low HDL-C. The use of PI was found to have both positive and negative effects with better selenium level but poorer HDL-C level and weight status.